Can Tirofiban Improve the Outcome of Patients With Acute Ischemic Stroke: A Propensity Score Matching Analysis - Cai, Lingxin; Yu, Xiaobo; Yu, Jun; Xu, Jing; Xu, Liang; Ling, Chenhan; Lou, Min; Yu, Cheng; Qian, Cong (Frontiers in Neurology, 2021)
Objective: To evaluate the efficacy and safety of tirofiban for patients with acute ischemic stroke (AIS), especially posterior circulation stroke (PCS). Methods: We enrolled 292 consecutive patients with acute ischemic stroke who suffered large artery occlusion (LAO) and underwent mechanical thrombectomy (MT) between January 2016 and May 2020. Patients were divided into two groups according to whether tirofiban was used during MT. The primary efficacy outcome was a favorable functional outcome, defined as a modified Rankin Scale (mRS) score of 0-2 at 3 months. The safety outcomes were the rate of mortality at 3 months and the presence of intracranial hemorrhage (ICH) and symptomatic intracranial hemorrhage (sICH). Cohorts were balanced using 1:1 propensity score matching (PSM). Subgroup analysis was further performed to compare the efficacy and safety of tirofiban between the anterior circulation stroke (ACS) and PCS groups. Results: A total of 292 patients were eligible for this study and divided into the tirofiban group (n=51) and the no-tirofiban group (n=241). In the propensity-score-matched cohort, the tirofiban group had a higher rate of favorable outcomes than the no-tirofiban group (49.0% vs 36.1%, P=0.043), and the mortality at 3 months showed a greater downward trend in the tirofiban group than the no-tirofiban group (15.6% vs 31.4% P=0.062). The risk of sICH and ICH was the same between the tirofiban and control groups (17.6% vs 23.5% P=0.463 and 31.3% vs 41.1% p=0.303, respectively). Tirofiban use was predictive of favorable outcomes (aOR 2.44; 95% CI 1.05 5.81; P=0.030) after multiple logistic regression analysis. Subgroup analysis revealed that tirofiban use was significantly associated with favorable outcomes in ACS (aOR 2.45; 95% CI 1.14 5.35; P=0.013) but not in PCS (aOR 1.25; 95% CI 0.26 10.69; P=0.570). Conclusion: We demonstrated that tirofiban administration was considerably safe and effective in AIS patients who underwent MT, significantly improving clinical outcomes without increasing ICH or sICH. Especially for difficult cases, the use of tirofiban may rescue more AIS patients. Furthermore, our results indicated that PCS patients seemed to benefit less, and more comprehensive randomized controlled trials are needed to confirm this finding.